Uterine artery embolization - K.D. Plaksiieva; N.V. Kosei; T.F. Tatarchuk; O.A. Vlasenko; V.S. Solskyy (Publishing House TRILIST, 2022)
Uterine fibroids (UF) is an extremely common benign tumor of the female reproductive system. This pathology is often associated with symptoms that significantly impair the quality of life of a woman and her working capacity, and can also affect the ability to conceive and gestation. Today, we have in the arsenal of operational, drug and minimally invasive methods of UF treatment. One of the most researched and at the same time rather controversial methods of UF treatment is uterine artery embolization (UAE). Literary sources were reviewed using the MEDLINE, PubMed and Web of Science databases for the period 2011-2021. The data related to the history of the technique development, its implementation, indications and contraindications for UAE, its effect on the UF symptoms and on fertility were systematized and presented in this review. UAE as an independent method for the treatment of benign uterine tumors has 20 years of experience in the world and in Ukraine. The indications for UAE are symptomatic UF: profuse and/or prolonged menstruation, dysmenorrhea, compression of the pelvic organs, dyspareunia, frequent urination or urinary retention. Absolute contraindications for UAE are genital tract infections, pregnancy, doubts about the diagnosis, as well as contraindications to the use of X-ray contrast agents. The effectiveness of UAE is assessed by the manifestations of UF symptoms and by the degree of fibroids size reduction. The average node reduction in the diameter is 2.2 cm. The clinical efficacy index is 81-96, 70-100 and 46-100% respectively in the treatment of abnormal uterine bleeding, pelvic pain and symptoms of compression of adjacent organs. There is a decrease in the node volume by 25-60% within 3-6 months. Conclusions. UAE today is an effective and safe minimally invasive operation, which is a worthy alternative to hysterectomy and expands the possibilities of organ-preserving technologies if there is UF.